2005
DOI: 10.1001/archsurg.140.1.85
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Risk Factors for Complications Following Sentinel Lymph Node Biopsy for Melanoma

Abstract: Background: Sentinel lymph node biopsy has become routine in the staging of patients with cutaneous melanoma and is presumed to have fewer complications than elective regional lymph node dissection (RLND). However, little information is available to refute or support this assumption. Hypothesis: Risk factors for complications following sentinel lymph node biopsy (SLNBX) can be identified. Design: Retrospective medical record review. Patients and Methods: The medical records of 339 consecutive patients undergoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
23
5
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 17 publications
5
23
5
5
Order By: Relevance
“…In a single-site study evaluating outcomes following SLNB for penile cancer, rate of surgical site infection and abscess was 4% and seroma was 2%, which was similar to a multi-center study that demonstrated an infection rate of 3% and a seroma rate of 3.1% [7]. It is notable that rates of complications are significantly lower in retrospective studies, with overall complication rates reported from < 1% to 2% [8,9]. Nonetheless, comparing the risks of elective inguinal LN excision to the risks for excisions performed for clinical indications has some limitations because clinical procedures may involve multiple LN excisions or more extensive dissection [5][6][7][8][9][10].…”
supporting
confidence: 71%
“…In a single-site study evaluating outcomes following SLNB for penile cancer, rate of surgical site infection and abscess was 4% and seroma was 2%, which was similar to a multi-center study that demonstrated an infection rate of 3% and a seroma rate of 3.1% [7]. It is notable that rates of complications are significantly lower in retrospective studies, with overall complication rates reported from < 1% to 2% [8,9]. Nonetheless, comparing the risks of elective inguinal LN excision to the risks for excisions performed for clinical indications has some limitations because clinical procedures may involve multiple LN excisions or more extensive dissection [5][6][7][8][9][10].…”
supporting
confidence: 71%
“…Independent from prognostic value, SLN biopsy helps to identify patient groups who might benefit from adjuvant therapy. Finally, in a historical prospective, a negative SLN biopsy spares those patients from morbidity, which was associated with elective lymph node dissection (wound infections, permanent nerve injury, chronic lymphedema) [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, data regarding complications associated with SLN biopsy (including seromas, lymphocele, persistent lymphedema, infection, wound dehiscence, hematoma, transient nerve injuries, allergic reactions to blue dye) are very scarce in adults, and the rate of complications ranges between 4.6% and 33.0% [14,[19][20][21][22][23]. In children and adolescents, only 4 reports comment on complications.…”
mentioning
confidence: 99%
“…Complications arise in about 10 % of patients and include seromas, hematomas, wound infections, and, in rare cases, functional deficits and nerve lesions [153][154][155].…”
Section: R Gutzmermentioning
confidence: 99%